Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.7547/15-121
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Nail Consistency and Incidence of Ingrown Toenails in Young Male Runners

Abstract: Sports activity by young male runners whose nails have a hard consistency seems to be directly related to the high incidence of onychocryptosis in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Interestingly, the incidence of IN followed a bimodal distribution with respect to age (~15 and 50 years old), and these findings were similar to those from a previous study. 1 The high prevalence of IN among teenagers can be explained by the association between high physical activity and IN, 9 and the increased IN prevalence in older subjects is associated with its high prevalence in middleaged women. We reviewed previous studies and attempted to determine which factors caused this result and found a previous study that showed that the majority of IN cases occur in men in their second and third decades and that the affected male : female ratio was approximately 2:1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the incidence of IN followed a bimodal distribution with respect to age (~15 and 50 years old), and these findings were similar to those from a previous study. 1 The high prevalence of IN among teenagers can be explained by the association between high physical activity and IN, 9 and the increased IN prevalence in older subjects is associated with its high prevalence in middleaged women. We reviewed previous studies and attempted to determine which factors caused this result and found a previous study that showed that the majority of IN cases occur in men in their second and third decades and that the affected male : female ratio was approximately 2:1.…”
Section: Discussionmentioning
confidence: 99%
“…Ingrown nails are believed to have a bimodal presentation, presenting between the first and third decades and then in the elderly [1,2]. One study reported that nearly 40% of 21-year-olds with a nail disorder had onychocryptosis [6]. However, in a recent cross-sectional study performed in Spain, prevalence was 15.7% in a podiatric population with an average age of 54 years old, countering prevailing thought [7].…”
Section: Discussion Epidemiologymentioning
confidence: 97%
“…Improper nail trimming technique is a well-known risk factor for ingrown toenails [6]. While attempting to "round off" nail corners (nails should be cut straight across), patients may inadvertently create barbs and spicules.…”
Section: Risk Factors and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Digital formula and nail consistency were defined using the protocols previously published. 17,18 A distinction was made between the variables studied (preexisting physical factors) and the lesions, because lesions were not present at the start but developed during the hike. The variable existing "muscle alterations" was not defined because where these were reported, candidates were excluded because they would have had difficulty completing the hike.…”
Section: Variables and Measurements Instrumentsmentioning
confidence: 99%